Pseudoelastic deformation in Mo-based refractory multi-principal element alloys - Sharma, Aayush; Singh, Prashant; Tanner, Kirk; Levitas, Velary I; Liaw, Peter K; Balasubramanian, Ganesh; Arroyave, Raymundo; Johnson, Duane D (arXiv.org, 2021)
Phase diagrams supported by density functional theory methods can be crucial for designing high-entropy alloys that are subset of multi-principal\(-\)element alloys. We present phase and property analysis of quinary (MoW)\(_{x}\)Zr\(_{y}\)(TaTi)\(_{1-x-y}\) refractory high-entropy alloys from combined Calculation of Phase Diagram (CALPHAD) and density-functional theory results, supplemented by molecular dynamics simulations. Both CALPHAD and density-functional theory analysis of phase stability indicates a Mo-W-rich region of this quinary has a stable single-phase body-centered-cubic structure. We report first quinary composition from Mo\(-\)W\(-\)Ta\(-\)Ti\(-\)Zr family of alloy with pseudo-elastic behavior, i.e., hysteresis in stress\(-\)strain. Our analysis shows that only Mo\(-\)W\(-\)rich compositions of Mo\(-\)W\(-\)Ta\(-\)Ti\(-\)Zr, i.e., Mo\(+\)W\(\ge\) 85 at.%, show reproducible hysteresis in stress-strain responsible for pseudo-elastic behavior. The (MoW)\(_{85}\)Zr\(_{7.5}\)(TaTi)\(_{7.5}\) was down-selected based on temperature-dependent phase diagram analysis and molecular dynamics simulations predicted elastic behavior that reveals twinning assisted pseudoelastic behavior. While mostly unexplored in body-centered-cubic crystals, twinning is a fundamental deformation mechanism that competes against dislocation slip in crystalline solids. This alloy shows identical cyclic deformation characteristics during uniaxial \(\lt\)100\(\gt\) loading, i.e., the pseudoelasticity is isotropic in loading direction. Additionally, a temperature increase from 77 to 1500 K enhances the elastic strain recovery in load-unload cycles, offering possibly control to tune the pseudoelastic behavior.